KOLABORASI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA DI SMA NEGERI 3 BANDA ACEH - Lailatussaadah, Lailatussaadah; Nurmayuli, Nurmayuli; Ariska, Dinda (Universitas Islam Negeri Sumatera Utara Medan, 2024)
One of the keys to the success of the implementation of the P5 independent curriculum in schools is collaboration and communication between teachers and students. Therefore, it is necessary to collaborate to support the implementation of the P5 Independent Curriculum between teachers and students. This study aims to analyze how the collaboration in the implementation of P5 at SMA Negeri 3 Banda Aceh. This study uses qualitative methods with data collection techniques including non-participant observation, semi-structured interviews and documentation. The sampling technique was carried out by purposive sampling and snowball,. Data analysis uses data reduction, data presentation and conclusion drawn, so that the validity of the data is checked, namely with credibility, transferability, dependability, and confirmability. The results of the study show that the P5 collaboration carried out at SMA Negeri 3 Banda Aceh uses 3 forms of collaboration, namely collaboration between teachers and students, collaboration between teachers, and collaboration between teachers and the school environment. All forms of collaboration have stages of planning, implementation and evaluation of the project. Thus, the form of collaboration in the implementation of P5 can be applied in Senior High Schools in general